1987
DOI: 10.1002/jbt.2570020303
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of inhibition of rat brain (Na +‐K +)‐stimulated adenosine triphosphatase reaction by cadmium and methyl mercury

Abstract: The mechanisms of inhibition of rat brain Na+-K+-ATPase by cadmium chloride (CdCl2) and methylmercuric chloride (CH3HgCl) were studied in vitro by assessing the effects of these heavy metals on this enzyme and associated component parameters. Both the heavy metals significantly inhibited the overall Na+-K+-ATPase in a concentration-dependent manner with an estimated median inhibitory concentration (IC-50) of 3.2 X 10(-5) M for CdCl2 and 6 X 10(-6) M for CH3HgCl. Protection of enzyme against heavy metal inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Substrates such as amino acids and glucose are cotransported down the Na + gradient into the cellular compartment (Na + -dependent transport); the higher Na + /K + -ATPase activity may be indicative of higher metabolite transport into hepatic cells. Heavy-metal binding to sulphydryl groups has often been implicated in both Na + /K + -ATPase inhibition and physiological effects (Rajanna et al, 1983;Ahammadsahib et al, 1987;Bertoni and Sprenkle, 1991). The present results show that 10 mg/kg cadmium leads to a decrease of Na + /K + -ATPase activity in liver (see Table III), which indicates changes in the metabolism of substrates and the distribution of ions and affects weight gain of pigs.…”
Section: Discussionmentioning
confidence: 47%
“…Substrates such as amino acids and glucose are cotransported down the Na + gradient into the cellular compartment (Na + -dependent transport); the higher Na + /K + -ATPase activity may be indicative of higher metabolite transport into hepatic cells. Heavy-metal binding to sulphydryl groups has often been implicated in both Na + /K + -ATPase inhibition and physiological effects (Rajanna et al, 1983;Ahammadsahib et al, 1987;Bertoni and Sprenkle, 1991). The present results show that 10 mg/kg cadmium leads to a decrease of Na + /K + -ATPase activity in liver (see Table III), which indicates changes in the metabolism of substrates and the distribution of ions and affects weight gain of pigs.…”
Section: Discussionmentioning
confidence: 47%
“…Pollutants such as heavy metals easily enter living organisms and accumulate in several tissues [5–7]. It is well described that several heavy metals have a high affinity for the free electron pairs of the S‐H groups [5, 8]. Therefore, heavy metals irreversibly inhibit several enzymes of the metabolism at the same time, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Past experiments indicate that MeHg can interfere with Ca>-mediated synaptic mechanisms and cellular aerobic respiration (Atchison and Narahashi, 1982;Atchison, 1986Atchison, , 1987Atchison, , 1988McKay et al, 1986;Levesque and Atchison, 1988;Kauppinen et al, 1989;Komulainen and Bondy, 1987;Levesque et al, 1992;Ahammadsahib et al, 1987;Ally et al, 1984;Yee and Choi, 1992). Results from presynaptic recordings indicated that 50 M MeHg suppressed both presynaptic and postsynaptic excitability.…”
Section: Discussionmentioning
confidence: 94%
“…Evidence from studies of neuromuscular junction and cerebrocortical synaptosomes suggests that MeHg interferes with Ca>-mediated synaptic mechanisms via effects on Ca> stores within the nerve terminal ([Ca>] ) (Atchison and Narahashi, 1982;Atchison, 1986Atchison, , 1987Atchison, , 1988McKay et al, 1986;Levesque and Atchison, 1988;Kauppinen et al, 1989;Komulainen and Bondy, 1987;Levesque et al, 1992). Other experiments suggest that MeHg interferes with cellular aerobic respiration (Ahammadsahib et al, 1987;Ally et al, 1984;Yee and Choi, 1992).…”
mentioning
confidence: 92%